Thermo- and oxidation-responsive homopolypeptide: synthesis, stimuli-responsive property and antimicrobial activity. Issue 17 (3rd April 2019) - Liang, Ce; Wang, Xiaodan; Zhou, Rongtao; Shi, Hengchong; Yan, Shunjie; Ling, Ying; Luan, Shifang; Tang, Haoyu
Abstract : We present the design and synthesis of a side-chain functional polypeptide with a thioether spacer that is readily decorated to produce thermo- and oxidation-responsive polymers with antimicrobial activity. Abstract : A homopolypeptide with a thioether spacer and a reactive chloro side-chain end group, namely PBLG-S-Cl, can be readily prepared by n -butylamine initiated ring-opening polymerization of γ-4-(substituent)benzyl-l -glutamate acid based N -carboxyanhydride (NCA) monomer. Cationic polypeptides (PBLG-S-ImX, X = I, BF4 ) with upper critical solution temperature (UCST)-type thermo- and oxidation-responsive properties were prepared by nucleophilic substitution of PBLG-S-Cl and subsequent ion-exchange reaction. OEGylated polypeptides (PBLG-S-OEG7 ) with lower critical solution temperature (LCST)-type thermo- and oxidation-responsive properties were prepared by nucleophilic substitution of PBLG-S-Cl with NaN3 yielding PBLG-S-N3, followed by 1, 3-dipolar cycloaddition. CD analysis revealed a thermally stable α-helical conformation of the resulting cationic polypeptides in aqueous solution. The α-helical conformation and long hydrophobic spacer enable PBLG-S-ImX (X = Cl, I, BF4 ) samples with good growth inhibition of S. aureus . The antimicrobial activity of PBLG-S-ImX (X = I, BF4 ) samples was found to be temperature independent. Yet, the antimicrobial activity was affected by the oxidation of thioether bonds as well as the oxidation/degradation of counteranions.